Mitochondrial Dysfunction Inhibits Hypoxia-Induced HIF-1α Stabilization and Expression of Its Downstream Targets - van Gisbergen, Marike W.; Offermans, Kelly; Voets, An M.; Lieuwes, Natasja G.; Biemans, Rianne; Hoffmann, Roland F.; Dubois, Ludwig J.; Lambin, Philippe (Frontiers in Oncology, 2020)
mtDNA variations often result in bioenergetic dysfunction inducing a metabolic switch towards glycolysis resulting in an unbalanced pH homeostasis. In hypoxic cells, expression of the tumor-associated carbonic anhydrase IX (CAIX) is enhanced to maintain cellular pH homeostasis. We hypothesized that cells with a dysfunctional oxidative phosphorylation machinery display elevated CAIX expression levels. Increased glycolysis was observed for cytoplasmic 143B mutant hybrid (m.3243A>G, >94.5%) cells (p<0.05) and 143B mitochondrial DNA (mtDNA) depleted cells (p<0.05). Upon hypoxia (0.2%, 16h), genetic or pharmacological oxidative phosphorylation (OXPHOS) inhibition resulted in decreased CAIX (p<0.05), vascular endothelial growth factor (VEGF) and hypoxia-inducible factor 1-alpha (HIF-1α) expression levels. Reactive oxygen species (ROS) and prolyl‐hydroxylase 2 (PHD2) levels could not explain these observations. In vivo, tumor take (>500 mm3) took longer for mutant hybrid xenografts, but growth rates were comparable with control tumors upon establishment. Previously, it has been shown that HIF-1α is responsible for tumor establishment. In agreement, we found that HIF-1α expression levels and the pimonidazole-positive hypoxic fraction were reduced for the mutant hybrid xenografts. Our results demonstrate that OXPHOS dysfunction leads to a decreased HIF-1α stabilization and subsequently to a reduced expression of its downstream targets and hypoxic fraction in vivo. In contrast, hypoxia-inducible factor 1-alpha (HIF-2α) expression levels in these xenografts were enhanced. Inhibition of mitochondrial function is therefore an interesting approach to increase therapeutic efficacy in hypoxic tumors.